The Historical movement of the Islamic nation in the approach of Ahl al-Bayt (Peace Be Upon Them) (Czech Journal of Multidisciplinary Innovations, 2023)
The People of the House (peace be upon them) were keen to follow a sound approach to reforming the Islamic nation and confronting everything that might lead its children into deviation. They strived hard to implement the provisions of the Noble Qur’an and the Noble Prophet’s Sunnah, starting from the Almighty’s saying “They will not harm you except for [some] annoyance. And if they fight you, they will show you their backs [i.e., retreat]; then they will not be aided “ Following the approach of the Messenger of God (may God’s prayers and peace be upon him and his family) and his family (peace be upon them) in enjoining what is right and forbidding what is evil. The Ahl al-Bayt (peace be upon them) had a good example of the Messenger Muhammad (may God’s prayers and peace be upon him and his family) and they followed his approach to correct the course of the movement of history. And alert the Islamic nation to benefit from the traditions of past nations, and try to avoid the mistakes that led to the civilization and achievements of the nations that preceded the Islamic nation .